The Influence of Teachers' Professional Competence on the Quality of Learning at State Vocational Schools - Pupuk Setiyono; Nurkolis; Ngurah Ayu Nyoman Murniati (Lembaran Ilmu Kependidikan, 2025)
The problem in this study is the low quality of education in Indonesia, reflected in the HCI and HDI rankings. In SMK Negeri Blora Regency, the main challenge lies in the managerial competence of principals and professional competence of teachers in improving the quality of learning. This research is based on the concept of human resource quality in education, principals‘ managerial competence (Permendiknas No. 13 Year 2007), and teachers’ professional competence (SNP Article 28 Paragraph 3 point c). The purpose of this study is to analyse the effect of both competencies on learning quality in Blora district state vocational schools.  This research uses quantitative research approach and ex post facto research type. The number of research samples was 196 teachers using proportional random sampling. Data were collected using a questionnaire with a linkert scale. The analysis of this research includes descriptive analysis, requirements test, and hypothesis testing including simple linear regression analysis.  The results showed that the principal's managerial competence (153.98) and teachers' professional competence (142.3) were in the very good category, while the quality of learning (143.15) was quite good. From the hypothesis testing, it was found that there is a positive influence of the principal's managerial competence on learning quality expressed by the equation Y = 94.108 + 0.319X1, a correlation of 0.325 and a contribution of 42.1%. There is a positive influence of teacher professional competence on learning quality expressed by the equation Y = 94.108 + 0.319X2 with a contribution of 23.8%.